Creating an Acmeology-Based Inclusive Environment for Students from the Temporarily Occupied Territories - Natalia Marakhovska (Charles University, 2022)
A result of the undeclared Russo-Ukrainian war is the new concept of 'internally displaced persons', the majority of whom are young people looking for learning and vocational opportunities and for this a conducive environment is needed. This article illustrates the experience of Mariupol State University (Ukraine) in organising an acmeology-based inclusive environment that aims to reach the students' highest possible developmental potential and welfare.